Advances in ceramic matrix composites - Low, It-Meng (Woodhead Publishing series in composites science and engineering., 2014)
Ceramic matrix composites (CMCs) have proven to be useful for a wide range of applications because of properties such as their light weight, toughness and temperature resistance. This book summarizes key advances and types of processing of CMCs. Topics include: types and processing of CMCs, covering processing, properties and applications; nanoceramic matric composites, silicon carbide-containing alumina nanocomposites and advances in manufacture by various infiltration techniques including heat treatments and spark plasma sintering; properties of CMCs with chapters on Finite Element Analysis, tribology and wear and self-healing CMCs; applications of CMCs, including those in the structural engineering, nuclear and fusion energy, turbine, metal cutting and microelectronics industries. --